Anarkisme Epistemologi Paul K. Fayerabend dan Relevansinya dengan Berpikir Kritis dalam Pendidikan Islam - Ikhsan Setiawan; Astrifidha Rahma Amalia (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
Islamic education has an important role in building a civilization. the main priority of an education system is educating students on how to learn and think critically, but Islamic education is considered to have not been able to achieve this target. Paul K. Feyerabend was a philosopher with the great thought of anarchism epistemology, the basic principle of his thought is anything goes. He argues that there should be no need to be too rigid in using a method or theory. Because none of these methods are perfect, it could be that the methods or theories that we believe and use are not actually theories. This study uses a qualitative approach with the method used, namely library research, by collecting related literature and analyzing it. Paul Feyerabend teaches us to always be critical in understanding things and use diverse perspectives, so it is not easy to blame different understandings. The theory presented by Paul is very relevant to Islamic Education which ideally is very open to critical space and open to all ideas or ideas that differ from our opinions. So that the book of Jesus is wiser and not easy to blame other opinions.